Juvenile pilocytic astrocytomas: A search for prognostic markers - Osman, Naeem (Department of Pathology, 2023)
Introduction: Juvenile pilocytic astrocytomas are one of the most frequent central nervous system tumours occurring in children. While they are classified as WHO Grade I tumours, their natural progression is difficult to predict with some patients suffering significant morbidity and mortality despite showing similar light microscopic features. Activation of the MAPK pathway of cell proliferation is a consistent finding in these tumours. Studies of these tumours are largely aimed at components of this pathway in an effort to establish reliable prognostic and predictive markers. Aims and objectives: Our study was aimed at reviewing the light microscopic features and also evaluating the BRAF, p16 and protein kinase ERK components of the MAPK pathway. The findings thereof were correlated with the clinical picture to establish if these markers have any prognostic or predictive value. Materials and methods: The total number of cases retrieved was 62. The light microscopic findings were evaluated. The cases were analysed for overexpression of BRAF by fluorescence in-situ hybridisation and p16 and pERK by immunohistochemistry. Our findings were considered statistically significant if P < 0.05. Results: There were no specific light microscopic findings present in those cases associated with disease progression and recurrence. BRAF overexpression was associated with better clinical outcomes (P=0.03). There was no statistically significant correlation between p16 and pERK expression and patient outcomes. Conclusion: Overexpression of BRAF in juvenile pilocytic astrocytomas is associated with better clinical outcomes. BRAF may still serve as a therapeutic target and reduce risks associated with surgery, especially in tumours that are not surgically accessible. Further evaluation of p16, pERK and other components of the MAPK pathway of cellular proliferation will undoubtedly be useful in identifying therapeutic targets for those patients who experience disease recurrence and progression.